Association Study of Dental Caries and Jaw Development in Patients with Unilateral Cleft Lip and Palate - GOTO, Takahiro; TENGAN, Toshimoto; SUNAKAWA, Hajime; ZHU, Haiying; ARAKAKI, Keiichi (Journal of Japanese Cleft Palate Association, 2012)
Objective: The aim of this study was to verify the association between dental caries and jaw development in patients with unilateral cleft lip and palate (UCLP). Subjects: Plaster models were prepared for 27 subjects in an occlusion care (OC) group and 39 subjects in a non-occlusion care (NOC) group. The occlusal surface was photographed and various dental arch parameters were measured. A t-test was used for each variable to examine significant differences between the groups. Results: The prevalence of dental caries in the OC group was lower than in the NOC group. The mean number of decayed-filled-teeth (dft) was 2.30 in the OC group, and 4.44 in the NOC group. There was no significant difference between the groups in the width and length of the maxillary and mandibular dental arches. The maxillary dental arch in the severe caries (SE-C) group and the slight caries (SL-C) group of the OC group was asymmetrical; however, it was symmetrical in the non-caries (N-C) group. The maxillary dental arches in the SE-C, SL-C and N-C groups of the NOC group were asymmetrical, whereas the mandibular arch was symmetrical in all groups. The tongue space volumes of the OC group and NOC group were similar. When compared to the control group, both groups showed significantly smaller values. The highest rate of midline shift was seen in the SE-C group, followed by the SL-C group, the N-C group and the control group. The angle of the alveolar cleft in the anterior region in the SE-C group was significantly larger than in the SL-C group and the N-C group. Conclusion: Our results revealed an association between dental caries and development of the jaw in patients with UCLP. It suggests that care of the occlusion at an early stage is necessary during treatment for UCLP.